Sex differences in the association between fasting glucose and ischemic stroke incidence in people without diabetes: a 19-year prospective cohort study in Korea - Hyun Yi Kook; U Chul Ju; Yong Soo Cho; Eujene Jung; Hyun Ho Ryu (Journal of Men's Health)
This study aimed to determine whether high fasting blood glucose (FBG) levels are a risk factor for ischemic stroke (IS) in the population without diabetes and conduct an interaction analysis to explore the potential differential effects of FBG levels and sex on IS risk. We used data from the Genome and Epidemiology Study (KoGES). The primary exposure was serum FBG obtained at the first interview. The main outcome was the occurrence of IS in the biennial follow-up surveys. Cox proportional regression analysis was performed to estimate the effects of high FBG on IS incidence. We performed an interaction analysis to examine the effect of FBG and sex interaction on the incidence of IS. Over the 18-year follow-up period, which included 5682 participants, 333 cases of newly diagnosed IS were recorded, equivalent to 5.5 cases per 1000 person-years. Elevated FBG levels did not show a significant impact on IS incidence, with an adjusted hazard ratio (aHR) of 1.06 (95% confidence interval (CI): 0.89–1.26). However, in the interaction analysis, elevated FBG was linked to a higher IS risk in females (aHR: 1.40; 95% CI: 1.03–1.92), while no statistically significant association was observed in males (aHR: 1.07; 95% CI: 0.87–1.48). In the population without diabetes, high FBG (≥100 mg/dL) was associated with an increased risk of IS only in females. This conclusion underscores the need for sex-specific strategies in managing and mitigating the risk of IS associated with high FBG. Even in the absence of diabetes, carefully monitoring and managing high FBG are crucial.